Case Report: Isolated Cystic Dilatation of the Cystic Duct: A Misdiagnosed Case Preoperatively - Jiankang Zhang; Zeming Hu; Xuan Lin; Dongliang Zhang; Hao Wang; Bin Chen (Frontiers in Surgery, 2021)
A 33-year-old female with a mild elevation of liver transaminase was sent to the general surgery department for medical services due to upper-right abdominal pain for 2 weeks. A liquid dark area ~4 × 3 × 3 cm in size in the theoretical location of the pancreatic segment of the common bile duct was detected by abdominal CT with no enhancement of the cystic wall found in the enhanced CT scan. The patient was then diagnosed with a choledochal cyst based on the results of the radiological images preoperatively. During the operation, the isolated cystic dilatation was found in the middle part of the cystic duct, and its caudal portion was found behind the head of the pancreas and converged into the common bile duct at an acute angle and low insertion. According to the intraoperative evaluation, the female was then diagnosed with a cystic duct cyst (CDC). The surgery was converted to a laparotomy for the unclear structure and the possibility of anatomic variation of the bile duct. The caudal portion of the cystic duct was found communicated with the common bile duct with a narrow base, and the extrahepatic bile duct was not cystic. The CDC was removed in the surgery. One week later, the patient was discharged from the hospital for the disappearance of abdominal pain and normal liver transaminase and did not report any discomfort in the 1-month-long follow-up. The lessons drawn from this case were as follows: (1) the distinction between the relatively frequent choledochal cyst and the isolated CDC should always be taken in mind; (2) a surgical strategy should be given priority for an intraoperatively confirmed CDC; (3) a common bile duct exploration is recommended for patients with choledocholithiasis or jaundice.